Pengembangan Model Konseling Kelompok Teknik Musik Terapi Nature Sound Untuk Mereduksi Academic Anxiety Siswa di SMP IT Faris Abdul Majid - Zulaifi, Reza; Mustakim, Ichwanul; Iman, Nurul (Jurnal Bimbingan dan Konseling Islam, 2024)
This study aims to develop and examine the effectiveness of a group counseling model utilizing nature sound music therapy techniques to reduce students' academic anxiety. Academic anxiety is a significant psychological barrier that affects students' concentration, motivation, and academic achievement. The research employed a Research and Development (R&D) method with a quantitative approach. The research subjects were students from SMP IT Faris Abdul Majid, selected using purposive sampling techniques. Data were collected through academic anxiety scale measurements conducted before (pretest) and after (posttest) the intervention, utilizing a quasi-experimental design involving experimental and control groups. The results indicate that the group counseling model based on nature sound music therapy techniques is significantly effective in reducing students' academic anxiety (p < 0.05). Students in the experimental group experienced a reduction in anxiety from a high to a moderate level, whereas the control group did not show significant changes. The intervention involved group discussions, reflections, and exposure to anxiety-provoking situations to train emotional regulation and relaxation skills. This study provides theoretical and practical contributions to the field of guidance and counseling, particularly through the application of nature sound music therapy as an innovative approach to addressing academic anxiety. The findings are recommended for implementation in school counseling services to support the holistic development of students' mental health and potential.